LUBA-SHANKADI VOCAL MUSIC No. 2 in a series of African music recordings issued by the Royal Museum of Central Africa, Tervuren, Belgium and the Belgische Radio en Televisie, 1969. 12-inch disc with pamphlet in four languages, pp. 83. - Tracey, Andrew (International Library of African Music, 1970)
A disc of recordings made by Father Tempels from 1944 to 1950, with musicological notes by Jos Gansemans.
Keywords: African Music